Proteomics of plasma-derived extracellular vesicles from human patients identifies biomarkers for monitoring visceral leishmaniasis therapy - Torres, Ana; Montero-Calle, Ana; Lozano-Rendal, Marina; Sánchez, Carmen; Bernardo, Lorena; Solana, Jose Carlos; San Martin, Juan Victor; Barderas, Rodrigo; Moreno, Javier; Carrillo, Eugenia (Frontiers in Immunology, 2025)
IntroductionThe most severe form of leishmaniasis, visceral leishmaniasis (VL), lacks standardized validated early predictors of treatment success or relapse. To distinguish between active infection and successful treatment, we searched for protein biomarkers in plasma-derived extracellular vesicles (EVs).MethodsThe proteomic profiles of EVs from immunocompetent patients with active VL (n=12) or 1, 3, or 6 months after completing a standard treatment regimen (n=12 each) were analyzed by LC-MS/MS. Six candidate biomarkers were further tested by ELISA in whole plasma.Results132 human proteins were differentially expressed in active VL- versus successfully treated patients. Pathway analysis identified pathogenic mechanisms associated with VL and pathways related to effective cure. SAA is directly measurable in whole plasma and exhibits differential expression levels, emerging as a promising, easily measurable, non-specific prognostic biomarker for patient management. Remarkably, we also identified Leishmania spp. proteins in EV samples, indicating a new source of parasite biomarkers in human samples.ConclusionPlasma EVs contain protein biomarkers that can be used to monitor the response to treatment, some of which are detectable in whole plasma after 1 month of treatment. Our study also provides a proteomic landscape of plasma EVs involved in VL, offering insight into the pathogenesis of this complex disease.